Continuous Self-Cycling Fermentation Leads to Economical Lycopene Production by Saccharomyces cerevisiae - Wang, Zhiming; Li, Xiangyu; Yu, Chao; Lu, Shuhuan; Xiong, Shuting; Yuan, Yingjin (Frontiers in Bioengineering and Biotechnology, 2020)
The economic feasibility and waste treatment problem are challenges to the industrialization of lycopene production from Saccharomyces cerevisiae. In this study, fermentation wastewater, biomass residue and residual D-galactose are recycled for lycopene production. Results show that when fresh water is totally replaced by wastewater, lycopene titer attains 1.21± 0.02 g/L, which is 14.2% higher than the fresh water group (P<0.05). An 80% replacement ratio of yeast extract by biomass residue causes no significant difference to lycopene production while 100% replacement ratio significantly lowers lycopene titer compared with the yeast extract group. Then, a novel fermentation medium containing wastewater and biomass residue with supplementing 3 g/L yeast extract and D-galactose is used for lycopene production. Lycopene titer increases 22.4% than the traditional fermentation in shake flasks (P<0.05). Continuous self-cycling strategy using wastewater and biomass residue was tested in shake flasks. The mean lycopene titer of the first 5 recycles shows no significant difference with the start batch. Scaling up to 70 L fermenter, the mean lycopene titer attains 5.88± 0.15 g/L in 3 recycles, which is 22.25% higher than the start batch (P<0.05). Economic analysis shows that the lowest unite product cost is achieved when 4 recycles are accomplished, which is 29.6% lower than the traditional fermentation while the chemical oxygen demand decreases 64.0%. Our study shows that continuous self-cycling fermentation process for lycopene production is feasible for the first time. The comprehensive utilization of wastewater and biomass residue from lycopene production by S. cerevisiae and achievement of high lycopene titer will hopefully accelerate industrialization of microbial production of lycopene.